Comparison of perioperative serum osteocrin concentrations between surgical techniques in dogs with cranial cruciate ligament rupture. (May 2023) - Isaka, Mitsuhiro; Konno, Wataru; Kokubo, Daiki; Udagawa, Hiromu; Hizuka, Sho; Sakai, Toshikazu; Yamamoto, Shushi; Torisu, Shidow; Ueno, Hiroshi
Abstract: The cranial cruciate ligament (CCL) rupture is a common orthopedic disease in dogs that is usually managed with tibial plateau leveling osteotomy (TPLO) or extracapsular lateral suture (ECLS). Osteotomy is generally associated with some complications, including nonunion. The periosteum plays an important role in bone growth and remodeling. Osteocrin (OSTN), which was recently identified and is involved in bone formation and differentiation, is produced in the periosteum and osteoblasts. The aimed to investigate whether the concentrations of serum OSTN change before and after stifle surgery in dogs and compare the OSTN concentrations in the two surgical techniques (TPLO: n = 20 vs. ECLS: n = 36). The postoperative serum OSTN concentration in the TPLO group was significantly lower than the preoperative value ( p < 0.05), while serum OSTN concentrations differed statistically between the preoperative and suture-removal periods. In contrast, no significant differences were observed in the ECLS group. In conclusion, osteotomy affects serum OSTN concentrations during the perioperative period in dogs, which may be related to periosteal injury. Highlights: Changes in osteocrin levels before and after stifle surgery were investigated. Osteotomy was shown to affect the perioperative osteocrin levels. The effects of osteotomy on osteocrin levels may reflect periosteum injury.